Plant-Dependent Soil Bacterial Responses Following Amendment With a Multispecies Microbial Biostimulant Compared to Rock Mineral and Chemical Fertilizers - Mickan, Bede S.; Alsharmani, Ahmed R.; Solaiman, Zakaria M.; Leopold, Matthias; Abbott, Lynette K. (Frontiers in Plant Science, 2021)
Biostimulants are gaining momentum as potential soil amendments to increase plant health and productivity. Plant growth responses to some biostimulants and alternative fertilisers could increase soil microbial diversity and provide greater plant access to less soluble nutrients. We assessed an agricultural soil amended with a multispecies microbial biostimulant in comparison with two fertilisers that differed in elemental solubilities to identify effects on soil bacterial communities associated with two annual pasture species (subterranean clover and Wimmera ryegrass). The treatments applied were: a multispecies microbial biostimulant, a rock mineral fertiliser at a rate of 15kg ha-1 phosphorus, a chemical fertiliser at a rate of 15kg ha-1 phosphorus, and a negative control with no fertilizer or microbial biostimulant. The two annual pasture species were grown separately for 10 weeks in a glasshouse with soil maintained at 70% of field capacity. Soil bacteria were studied using 16S rRNA with 27F and 519R bacterial primers on the Mi-seq platform. The microbial biostimulant had no effect on growth of either of the pasture species. However, it did influence soil biodiversity in a way that was dependent on the plant species. While application of the chemical and mineral fertilisers each increased plant growth, both were associated with the lowest alpha diversity of the soil bacterial community (e.g. Fisher and Inverse Simpson indices). Additionally, these responses were plant-dependent; soil bacterial OTU richness was highly correlated with soil pH for subterranean clover (R2 =0.61) but not for Wimmera ryegrass. Soil bacterial richness was lowest following application of each fertiliser when subterranean clover was grown. In contrast, for Wimmera ryegrass, soil bacterial richness was lowest for the control and the mineral fertiliser. Beta diversity at the bacterial OTU level of resolution by permanova demonstrated a significant impact of soil amendments, plant species and an interaction between plant type and soil amendments. This experiment highlights the complexity of how soil amendments, including microbial biostimulants, may influence soil bacterial communities associated with different plant species, and shows that caution is required when linking soil biodiversity to plant growth. In this case, the microbial biostimulant influenced soil biodiversity without influencing plant growth.